The Historical State, Local Collective Action, and Economic Development in Vietnam - Dell, Melissa; Lane, Nathan; Querubin, Pablo (Econometrica, 2018)
This study examines how the historical state conditions long‐run development, using Vietnam as a laboratory. Northern Vietnam (Dai Viet) was ruled by a strong, centralized state in which the village was the fundamental administrative unit. Southern Vietnam was a peripheral tributary of the Khmer (Cambodian) Empire, which followed a patron‐client model with more informal, personalized power relations and no village intermediation. Using a regression discontinuity design, the study shows that areas exposed to Dai Viet administrative institutions for a longer period prior to French colonization have experienced better economic outcomes over the past 150 years. Rich historical data document that in Dai Viet villages, citizens have been better able to organize for public goods and redistribution through civil society and local government. We argue that institutionalized village governance crowded in local cooperation and that these norms persisted long after the original institutions disappeared.